Proposal of a model of knowledge management to research in private universities of Huánuco región - López-Sánchez, Jorge L. (2019)
Nowadays, private universities of our country are being questioned because of the lack of knowledge production as a result of scarce scientific research works, and this is due to various factors, such as: low budget for this purpose, specialized laboratories without the necessary equipment, bibliographic information not current, untrained professors in science and technology, professors who teach investigation without the research training, no communication with society to identify lacks and needs, among others. With the intention of solving this problem, in this research a model of knowledge management is proposed for research in private universities in Huánuco Region, to allow analyzing the processes of creation and transfer of knowledge, then, determine the key factors of success; promoting interdependence between the intellectual capital and knowledge management process.